1981
DOI: 10.1002/ar.1092000206
|View full text |Cite
|
Sign up to set email alerts
|

Developmental changes in the fine structure of the chorion laeve (Smooth chorion) of the rhesus monkey placenta

Abstract: Developmental changes in the fine structure of the chorion laeve (smooth chorion) of the rhesus monkey were studied at two time periods during gestation: 1) Early (19-60 days of gestation), before the chorionic epithelium fuses with the parietal decidua, and 2) near term, when the fused chorioamnion has also fused with the parietal decidua. Early in gestation the chorionic epithelium consisted of columnar and cuboidal cells one or two layers thick. The apical border of the cells had microvilli and coated pits,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
6
0

Year Published

1985
1985
1998
1998

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 31 publications
2
6
0
Order By: Relevance
“…Additional immunohistochemical analyses are needed to resolve this issue. The presence of microfibrils was consistent with earlier studies of macaque amnion, chorion laeve, and cytotrophoblastic shell where similar microfibrils were abundant (King, 1980(King, , 1981Blankenship, 1993, 1994). Microfibrils have also been described in human fetal membranes (Modesti et al, 1984;Aplin et al, 1985;Malak et al, 1993).…”
Section: Discussionsupporting
confidence: 89%
“…Additional immunohistochemical analyses are needed to resolve this issue. The presence of microfibrils was consistent with earlier studies of macaque amnion, chorion laeve, and cytotrophoblastic shell where similar microfibrils were abundant (King, 1980(King, , 1981Blankenship, 1993, 1994). Microfibrils have also been described in human fetal membranes (Modesti et al, 1984;Aplin et al, 1985;Malak et al, 1993).…”
Section: Discussionsupporting
confidence: 89%
“…The macaque placenta is anatomically similar to that of humans [24][25][26][27][28][29][30] and produces progesterone 21 as does the human placenta. Organogenesis in macaques is also comparable with humans.…”
mentioning
confidence: 99%
“…The ultrastructure of the membranous chorion of the rhesus monkey placenta early in gestation has been described in detail elsewhere (King, 1981). Therefore, only those features pertinent to this study will be described, specifically the vacuolar apparatus which includes the endocytic complex and Golgi-lysosomal system.…”
Section: Resultsmentioning
confidence: 99%
“…As a result of superficial implantation in the macaque monkey, the membranous chorion is exposed to the uterine lumen during early gestation. Morphological studies have suggested that this epithelium may be absorptive, possibly taking up macromolecules from the uterine lumen (King, 1981). The suggestion is also supported by the observations that similar cells in other species have been shown to have a n absorptive or phagocytic function (for references see Dantzer, 1982;Burton, 1982;King, 1982a,b;1984).…”
mentioning
confidence: 91%
See 1 more Smart Citation